The effectiveness of multicomponent pressure injury prevention programs in adult intensive care patients: A systematic review. (February 2020) - Lin, Frances; Wu, Zijing; Song, Bing; Coyer, Fiona; Chaboyer, Wendy
Abstract: Background: Pressure injuries are potentially preventable but frequently occurring adverse events. Intensive care patients have major risk factors for pressure injury with a reported pressure injury prevalence of 12–33%. Multi-faceted interventions, also known as programs or care bundles, are recommended to prevent pressure injuries. Aim: This systematic review evaluated the effectiveness of pressure injury prevention programs in reducing pressure injury prevalence and incidence in the adult intensive care population. It also critically appraised the program components and strategies used to implement these programs. Method: We searched PubMed, EMBASE (embase.com), Ovid MEDLINE, EBSCOhost CINAHL, and Cochrane Library databases separately for papers published in English and Chinese from the year of 2000 to May 2018. After removing duplicates, two authors independently screened the title and abstracts, then full-text against the inclusion and exclusion criteria. Data was extracted by one author and checked by a second author. Quality appraisal was conducted by two authors by using the Quality Improvement Minimum Quality Criteria Set, and the Mixed Methods Appraisal Tool. Content analysis was used to categorise program components. Implementation strategies were grouped into six classifications: dissemination strategies, implementation process strategies, integration strategies, capacity building strategies, sustainability strategies, and scale up strategies. Results: Twenty-one peer reviewed papers (12 quality improvement projects, and 9 research papers from 8 studies) were included. Pressure injury prevention programs with 2–11 components were commonly implemented. Common components of the programs included: clarification of staff roles, introducing new roles, repositioning, staff and patient education, support surfaces use, pressure injury risk assessment, skin assessment, nutrition needs assessment, documentation, multidisciplinary team involvement, and mobilisation. Implementation strategies commonly used were education, audit and feedback, and standardising documentation. Five of the eight research studies and one of the quality improvement projects reported significant decrease in pressure injury prevalence, and/or increase in compliance to pressure injury prevention protocols and strategies. Two quality improvement papers reported cost savings of $1 million and £2.6 million respectively after the implementation of the programs. Conclusion: Much of the work on multicomponent pressure injury prevention programs has been undertaken as quality improvement projects and before and after research studies with limited rigour. However, positive outcomes and strong theoretical rationales for the components in the programs suggest that they are beneficial. This calls for future high-quality research such as randomised controlled trials to test the effectiveness of multicomponent interventions and their implementation strategies. Tweetable abstract : Some multicomponent pressure injury prevention programs were found to be effective; however, higher level of research evidence is needed.